Effectiveness of Social-Psychological Service in the Prevention of Adolescents with a Difficult Education - Abdukakhorova Gulnoza Abdurasulovna (Researchparks Publishing, 2022)
Legal documents are important for teachers and psychologists in practical work with adolescents with deviant behavior and difficult upbringing. The practical aspects of social-psychological service in conducting psychoprophylactic work on the problem of deviant behavior in adolescents are highlighted.